LETTERS. - Brooks, George A.; Curtis, Robert Kern; Alma, Sally Benziger; Donovan, Victor J.; Floretta, M. (America Magazine: The Jesuit Review of Faith & Culture, 1979)
Several letters to the editor are presented in response to articles in previous issues including "Into the Mainstream," by John W. Donohue in the April 14, 1979 issue, "Whose Keeping School?," issued in the May 5, 1979 issue, and "Remembering," by William V. Dych in the March 31, 1979 issue.